The Impact of Tomato Growing on The Socio-Economic Welfare of The People of Katete Sub-County Kanungu District. - Munvaneza, Francis (Kabale University, 2024)
The purpose of this study was to assess the impact of tomato growing on the socio-economic welfare of the people of the Katete sub-county Kanungu district.